On approximation by Stancu variant of Bernstein-Durrmeyer-type operators in movable compact disks - Yu Danshegn; Pang Zhaojun (Demonstratio Mathematica)
In this study, we introduce a kind of Stancu variant of the complex Bernstein-Durrmeyer-type operators in movable compact disks. Their approximation properties for analytic functions in the movable compact disks are investigated.